Approaches to the History of Philosophical Concepts: Intersections of the History of Philosophy with Intellectual History and Conceptual History - Manzo, Silvia (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
This article addresses historiographical questions about the concepts by which philosophy attempts to provide answers to the problems it poses. It argues for a view of philosophy as a historically dynamic intellectual practice that has no clear and fixed boundaries separating it from other disciplines. It proposes that the history of philosophy should be practiced as a kind of history that lies within, rather than outside, intellectual history. It shows that philosophical concepts are sometimes born and persist within philosophy, sometimes die without passing through philosophy, and sometimes come from or migrate to other disciplines. It also argues that the methodology of conceptual history can be helpful in the study of philosophical concepts. The article concludes that the history of philosophy is relevant in its own right and suggests how the new histories of philosophy written from postcolonial, global, and feminist perspectives are a clear example of this.